Effects of mouldboard shape and operational parameters on soil-ridger dynamics: An experimental and discrete element modelling approach - Avdhoot Walunj; Saurabh Shinde; Sachin Nalawade; Pranav Pawase; Zhiwei Zeng (Smart Agricultural Technology)
This study provides an in-depth investigation of soil-ridger interactions through both experimental analysis and discrete element method (DEM) simulations. The research examines how variations in ridger mouldboard shapes (flat, concave, and convex), operating depths (100, 140, and 180 mm), and speeds (2, 3, and 4 km/h) affect furrow width, furrow depth, ridge height, draft force, and soil profile characteristics. Field experiments on sandy clay loam soil incorporated 27 unique treatment combinations. The DEM-based soil-ridger interaction model, developed with Hertz-Mindlin contact mechanics and bonding contacts, was validated through angle of repose test. Analysis of the data revealed that mouldboard shape has a significant effect on furrow geometry: concave mouldboard produced wider, deeper furrow, while convex mouldboard resulted in narrower, shallower furrows. Speed and depth also played influential roles, with higher speed and deeper operation resulting in wider, shallower furrows and increased draft force. Ridge and furrow profile indicated that mouldboard shape, speed, and depth collectively shaped soil topography. The average relative error between experimental and DEM data for furrow width, furrow depth, ridge height, and draft force ranged between 2.75% and 17.26%, demonstrating close agreement. This study confirms that DEM simulation is a robust and effective method for analyzing soil-ridger interactions.